Beyond seasoning nutrients bioactive ingredients and healthcare effects of Allium vegetables - Ahmed, Hafiz Ghulam Muhu Din; Yang, Jiazhen; Zhu, Tong; Iqbal, Rashid; Sheng, Qing; Dong, Ruijie; Tian, Wenhuai; Xiao, Lei; Zeng, Yawen; Ding, Yumei (Frontiers in Nutrition, 2025)
This review highlights the nutritional and therapeutic significance of Allium vegetables—including garlic, onion, leek, and chive—emphasizing their principal bioactive compounds such as organosulfur compounds, flavonoids, and essential micronutrients. These phytochemicals exhibit potent antioxidant, anti-inflammatory, and anticancer activities that contribute to the prevention and management of chronic diseases including cancer, diabetes, and cardiovascular disorders. Mechanistic studies indicate that Allium-derived compounds modulate oxidative stress and inflammatory pathways through NF-κB and Nrf2 signaling, thereby enhancing metabolic and immune resilience. Despite these well-established benefits, challenges such as low bioavailability, inter-species variability, and limited clinical validation restrict translational potential. Recent advances in nanoencapsulation, emulsion-based delivery, and inclusion complexes offer promising strategies to improve compound stability and absorption. Future research should integrate clinical validation, comparative genomics, and functional food formulation to maximize health outcomes. This review underscores Allium vegetables as promising functional foods for preventive healthcare and supports their integration into daily diets to promote sustainable wellbeing.